2021
DOI: 10.1177/1971400920983678
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of apparent diffusion coefficient in differentiation of glioblastoma from metastasis

Abstract: Background Brain metastasis and glioblastoma multiforme are two of the most common malignant brain neoplasms. There are many difficulties in distinguishing these diseases from each other. Purpose The purpose of this study was to determine whether the mean apparent diffusion coefficient and absolute standard deviation derived from apparent diffusion coefficient measurements can be used to differentiate glioblastoma multiforme from brain metastasis based on cellularity levels. Material and methods Magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In a study from Iran, the ADC values/ratios of GBM, metastases and of edemas did not differ significantly [ 28 ]. This is largely consistent with our results, in which we did not detect any differences if the ADC values were measured within the area of 1 cm and 2 cm away from the tumor edge.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Iran, the ADC values/ratios of GBM, metastases and of edemas did not differ significantly [ 28 ]. This is largely consistent with our results, in which we did not detect any differences if the ADC values were measured within the area of 1 cm and 2 cm away from the tumor edge.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging is a non-invasive MR technique for measuring the dispersion of water in the brain ( Messina et al, 2020 ). The Apparent Diffusion Coefficient (ADC) is a quantitative index calculated from DWI to quantify the diffusing capacity of water in tissues ( Beig Zali et al, 2021 ). DWI reflects whether the activity of water is restricted, showing a high or low signal if water activity is restricted or not, respectively.…”
Section: Principles and Applications Of Mri-related Techniques In Sae...mentioning
confidence: 99%
“…Also, intratumoral creatine suggests GBM, whereas its absence indicates metastasis when single-voxel proton MR spectroscopy is used for imaging [10,67]. A study examining the use of the mean apparent diffusion coefficient and absolute standard deviation derived from apparent diffusion coefficient measurements based on cellularity levels could not find marked differences between GBM tumors from brain metastasis [68]. However, other studies found that the apparent diffusion coefficient could differentiate GBM from metastasis, and that homogeneity and the inverse difference moment of GBM were significantly higher than those of metastases in the regions of interest placements examined [10,69].…”
Section: Brain Metastases Inflammation and Imagingmentioning
confidence: 99%
“…The presence of intratumoral creatine indicates GBM, whereas its absence indicates metastasis, in samples consisting of 11 anaplastic gliomas, 20 GBMs and 25 metastases [67] MRI No differentiation between GBM tumors and brain metastases when using the mean apparent diffusion coefficient and absolute standard deviation derived from apparent diffusion coefficient measurements based on cellularity levels (n = 34 patients) [68] MRI Use of the apparent diffusion coefficient could differentiate GBM from metastasis [69] Higher homogeneity and inverse difference moment in GBM compared to metastases (n = 36 GBMs and 26 metastases) MRI Heterogeneity of the GBMs peritumoral edema was significantly higher than the edema surrounding MET by texture analysis, allowing a differentiation with a sensitivity of 80% and specificity of 90% (n = 22 GBM tumors and 21 metastases) [ A prediction accuracy to 98.6% was reached by applying a confidence rate of 0.999 when images with substantial artifacts were excluded (n = 25 patients with GBM, brain metastasis or meningioma)…”
Section: Single-voxel Proton Mr Spectroscopymentioning
confidence: 99%